Pengembangan Bahan Ajar Berbasis Media Animasi pada Materi Menulis Teks Cerpen Siswa Kelas XI SMA Al-Washliyah Pasar Senen Medan - Effendi, Enggy Vistia; Andriany, Liesna; Rita, Rita (Medan Resource Center, 2024)
Teaching materials for writing short stories, delivered through animation-based modules, were developed for class XI students at SMA Al-Wasliyah Pasar Senen Medan. This Research and Development (R&D) study aimed to produce and assess the quality of these modules. Conducted with 25 students, the research involved five steps: (1) information gathering, (2) product development, (3) validation test, (4) product revision, and (5) product trial, utilizing both quantitative and qualitative analysis. Validation results showed high approval from material and media experts, with scores of 86% and 87% respectively. Analysis of short story writing scores revealed positive outcomes, with 18 students scoring above 75. Student feedback on the module's feasibility yielded a 90% approval rating. Thus, the developed teaching materials, utilizing animation media, are highly suitable for enhancing short story writing skills among class XI students at SMA Al-Wasliyah Pasar Senen Medan.